“Who exchanges what with whom?” – The role of social capital among entrepreneurs - Pohja, Tuija-Liisa (Piccola Impresa / Small Business, 2009)
This conceptual paper analyses why social capital is important for entrepreneurial intentions.The concept of social capital identifies a social component of factors that shapeeconomic growth. It argues that social capital has an important role both on individualand regional level for entrepreneurial activity. The contribution of social capital theory inunderstanding the entrepreneurial intentions remains rather under explored. The trust theymay be built between firms, networks and co-operative norms could facilitate a more rapidflow of information. This could have implications for entrepreneurial research. This paperdoes not attempt to treat all aspects of the concept of social capital. It is difficult to arriveto a precise definition of this term and this issue will be discussed. The working definitionis emerging in an interdisciplinary literature and refers to networks, norms and cooperationbetween individuals and groups. Some work measure trust (e.g. Coleman 1988, 1990)as a part of social capital but this study looks at trust as an outcome of social capital (e.g.Woolcock 2001). By providing a concise working definition of social capital, this paper analyseswhy it is important for entrepreneurial intentions and therefore also to policy-makersand regional development. The intension models are widely used and tested (e.g. Ajzen1985, 1991, Krueger 1993, Krueger et al. 2000) but they still leave some questions aboutbehaviour and the factors that influence it. Ajzen and Fishbein modified their model asrecently as 2005. Their latest model presents background factors and normative and behaviouralbeliefs. This paper also offers a discussion of how entrepreneurial intention modelscould be developed.